Distribution and Status of Podocnemis lewyana in the Magdalena River Drainage of Colombia (2009)
ABSTRACT: – We obtained evidence of the continued presence of Podocnemis lewyana in 18 different sites within the Magdalena River drainage of northern Colombia. However, abundances at most sites were low, even in areas where the species had previously been reported as common. Although hunting of adults is no longer commercially viable, local people consume individuals that are captured incidentally while fishing. Hunting of eggs during the incubation period each year continues to be intensive. Turtle abundances were negatively related to human densities throughout this area. In the Chicagua River, where turtle abundances were highest, we conducted standardized shoreline censuses of basking adults and documented abundances of approximately 6 individuals/km2 . Turtles often basked on mud banks, beaches, or emergent logs in aggregations made up of all size classes. Pilot trapping efforts also succeeded in capturing all size classes of turtles, which suggests that more intensive monitoring programs would be feasible. Given the evidence of declines in most areas of the range of this species, the current lack of regulation of its exploitation, and the projections for continued human population growth in this area, we recommend its International Union for Conservation of Nature (IUCN) status be changed from Endangered to Critically Endangered (CR A2acd)